Growth pole strategy and regional development policy : Asian experience and alternative approaches - Lo, Fu-chen.; Kamal Salih; United Nations (Oxford ; New York : Published for the United Nations Centre for Regional Development by Pergamon Press, 1978)
This is a critical review of industrialization strategies and the growth pole approach to planning in Asia is given in this book. Alternative development strategies appropriate to prevailing conditions in Asia are also covered.
"Papers presented at a seminar and symposium sponsored by the United Nations Centre for Regional Development."
Includes bibliographical references and index.
lje 16/5/18
Loans
Keywords: Regional planning; Economic development; Economic conditions; Central places